Narrative characteristics and reporting techniques of non-fiction texts of New Latin American Journalism, between 2002 and 2012. Analysis based upon non-fiction texts of teachers of Gabo Foundation. - Chian, Daniel Alejandro Robles (2021)
Similar to the journalism movement called «New Journalism» that was born in the United States, different journalists and writers in Latin America used literary genres tools to write non-fiction texts, maintaining the principles and practices of journalism. This movement was called «New Latin American Journalism». This study aims to identify and describe the narrative-characteristics and reporting-techniques of certain chronicles of New Latin American journalism between 2000 and 2012, based on the work of prominent writers from the Gabo Foundation. It is an applied research with a qualitative approach on a descriptive level. This study is non-experimental. The non-random sample is made up of 10 chronicles that meet four requirements: they have a length of 2500 words or more, describe a person, group of people or place, describe an extraordinary situation of an ordinary person or an ordinary behavior of a famous person, and describe a particular reality that allows us to understand a universal reality.